Results of the gravity field interpretation in the Turčianska Kotlina Basin - GRINČ, Michal; BIELIK, Miroslav; MOJZEŠ, Andrej; HÓK, Jozef (Contributions to Geophysics and Geodesy, 2010)
The paper deals with the quantitative interpretation of the gravity field inthe Turčianska Kotlina Basin. The interpretation was done by means of the applicationof the 2D density modelling method using the GM-SYS software. Geophysical constraintsof the density models are represented by the existing geophysical measurements and interpretations.The Turčianska Kotlina Basin in the picture of the regional gravity field ischaracterized by the local gravity low with amplitude of about 12 mGal. The source ofthis gravity low is low density Tertiary sediments, which fill the basin. From the Tertiarysediments the Neogene sediments play dominant role in observed gravity, because theirgravity effects are considerably larger in comparison with the gravity effects of the Paleogenesediments. The contacts between the Malá Fatra and Vel’k´a Fatra Mts., and theTurčianska Kotlina Basin are characterized by the significant gravity gradients. They reflecttectonic contact between the basin and crystalline core mountains. In the Turčianskagravity low we can see along the Profile TK-AL three local gravity lows. The highest localgravity low is explained by the largest thickness of the Tertiary sediments. Another twolocal gravity lows are also characterised by thicker layers of the Tertiary sediments. Densitymodels assume that the eastern (western) part of the basin basement is built by theMesozoic (crystalline) rocks. In the central part of the Profile TK-BL the thick Paleogenesedimentary filling (more than 1 km) compensates the deepest part of the Pretertiarybasement. Density model along the Profile TK-BL does not suggest a presence of thePaleogene sediments in the basin filling. It is also indicated that the Mesozoic rocks underliethe Tertiary sediments. The Pretertiary basement was interpreted in the depthsfrom 0 km up to the 2 km.